2002
DOI: 10.1161/hy0202.103469
|View full text |Cite
|
Sign up to set email alerts
|

Increased Renal Medullary Oxidative Stress Produces Hypertension

Abstract: Abstract-The present study examined whether chronic increased oxidative stress within the medulla of the kidney lowers medullary blood flow and leads to hypertension. Optical fibers were implanted into the renal cortex and medulla of uninephrectomized Sprague-Dawley rats (Harlan Sprague-Dawley, Madison, Wis) for the daily measurement of blood flow to these regions using laser-Doppler flowmetry techniques, while arterial pressure was measured from an indwelling aortic catheter. A renal medullary interstitial ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
155
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(166 citation statements)
references
References 41 publications
9
155
2
Order By: Relevance
“…33 In genetically hypertensive rats, the number of intrarenal superoxide-positive cells is positively correlated with systolic blood pressure levels. 14,34 Recently, resveratrol was shown to mitigate oxidative stress and normalize angiotensin signaling in the kidney and reduce blood pressure via activation of phase II antioxidant enzymes. 35 Aortic stiffening is associated with the development of hypertension.…”
Section: Interaction Of Oxidative Stress and Inflammation In The Devementioning
confidence: 99%
“…33 In genetically hypertensive rats, the number of intrarenal superoxide-positive cells is positively correlated with systolic blood pressure levels. 14,34 Recently, resveratrol was shown to mitigate oxidative stress and normalize angiotensin signaling in the kidney and reduce blood pressure via activation of phase II antioxidant enzymes. 35 Aortic stiffening is associated with the development of hypertension.…”
Section: Interaction Of Oxidative Stress and Inflammation In The Devementioning
confidence: 99%
“…Interstitial inflammation and angiotensin activity are also inevitably associated with oxidative stress that, in itself, is a significant influence that impairs sodium excretion. The role of oxidative stress in the renal medulla driving sodium retention has been extensively investigated by Cowley et al 67,68 Impaired pressure natriuresis and stimulated tubuloglomerular feedback have also been demonstrated in patients with hypertension. 69 The long-term effects of tubulointerstitial inflammation may also have a role in the progression of chronic renal disease.…”
Section: Impairment In Salt Excretion As a Consequence Of Renal Micromentioning
confidence: 99%
“…1 Consistent with these observations, longterm, medullary interstitial infusion of DETC led to a reduction of MBF and produced hypertension in the absence of changes in cortical blood flow. 2 Because the same dose of DETC when given intravenously neither reduced MBF nor changed arterial pressure, that study demonstrated that an increase in oxidative stress, specifically within the renal medulla, would result in hypertension.…”
mentioning
confidence: 93%
“…1,2 It has been shown in short-term, anesthetized-rat studies that medullary interstitial infusion of the superoxide dismutase (SOD) inhibitor diethyldithiocarbamic acid (DETC) reduces MBF and sodium excretion without a change in blood pressure. 1 Opposite changes were observed with medullary interstitial infusion of the cellpermeable SOD mimetic 4-hydroxytetramethylpiperidine-1-oxyl (TEMPOL).…”
mentioning
confidence: 99%